2019
DOI: 10.18203/2320-1770.ijrcog20196031
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factor analysis for post-partum depression in women: a cross-sectional study at tertiary care centre

Abstract: Background: Postpartum depression (PPD) is non-psychotic depressive episode that occurs between postpartum to fourteen months of childhood. It has adverse effect on mother and child health. Aim of this study was to analyze prevalence and risk factors for postpartum depression at tertiary care centre.Methods: This cross-sectional study was done in obstetrics and gynaecology department where 175 women between 10 days to 1 year of delivery were assessed using Edinberg postpartum depression scale. A score of 10 or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
1
0
Order By: Relevance
“…7 It is found that, in our study out of 150 mothers who developed PPD, 10 mothers with IUD babies developed postpartum depression and 96 mothers whose babies are having NICU admission developed postpartum depression, and 44 mothers developed PPD who had baby mother side and the studies conducted by Rahul Mathur et al, Kanchana Rani et al and Azad R et al, have also showed same results that there is increased incidence of PPD in mothers having adverse perinatal outcomes. 8,17,18 For all 150 mothers who had PPD, appropriate referrals were given to the department of Psychiatry and with reassurance, counselling and psychoeducation, they improved. No pharmacotherapy was required in 149 patients.…”
Section: Discussionmentioning
confidence: 99%
“…7 It is found that, in our study out of 150 mothers who developed PPD, 10 mothers with IUD babies developed postpartum depression and 96 mothers whose babies are having NICU admission developed postpartum depression, and 44 mothers developed PPD who had baby mother side and the studies conducted by Rahul Mathur et al, Kanchana Rani et al and Azad R et al, have also showed same results that there is increased incidence of PPD in mothers having adverse perinatal outcomes. 8,17,18 For all 150 mothers who had PPD, appropriate referrals were given to the department of Psychiatry and with reassurance, counselling and psychoeducation, they improved. No pharmacotherapy was required in 149 patients.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that the prevalence of PPD in primiparous mothers is between 10-15%, and this rate increases up to 35% depending on demographic factors [2] . PPD, which is characterized by feelings of sadness, anxiety and fatigue, has a significant negative impact on both mother and baby in the following years [3][4][5] .…”
Section: Introductionmentioning
confidence: 99%